Fenticonazole nitrate loaded trans-novasomes for effective management of tinea corporis: design characterization, in silico study, and exploratory clinical appraisal. (31st December 2022) - Albash, Rofida; Ragaie, Maha H.; Hassab, Mahmoud A. El; El-Haggar, Radwan; Eldehna, Wagdy M.; Al-Rashood, Sara T.; Mosallam, Shaimaa
Abstract: The current investigation aimed for loading fenticonazole nitrate (FTN), an antifungal agent with low aqueous solubility, into trans-novasomes (TNs) for management of tinea corporis topically. TNs contain Brij ® as an edge activator besides the components of novasomes (cholesterol, Span 60, and oleic acid) owing to augment the topical delivery of FTN. TNs were fabricated applying ethanol injection method based on D-optimal experiment. TNs were evaluated with regard to entrapment efficiency percent (EE%), particle size (PS), polydispersity index (PDI), and zeta potential (ZP). Further explorations were conducted on the optimum formulation (F7). F7 showed spherical appearance with EE%, PS, PDI, and ZP of 100.00 ± 1.10%, 358.60 ± 10.76 nm, 0.51 ± 0.004, and −30.00 ± 0.80 mV, respectively. The in silico study revealed the ability of the FTN–cholesterol complex to maintain favorable interactions throughout the molecular dynamics simulation (MDS) study. Moreover, Trichophyton mentagrophytes growth was inhibited effectively by F7 than by FTN suspension applying 2, 3-bis(2-methyloxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide (XTT) reduction assay. Furthermore, a clinical appraisal on patients with tinea corporis fungal lesions confirmed the superiority of F7 compared to Miconaz ® cream in the magnitude of clinical cure of tinea corporis. Thereby, TNs could be considered as promising vesicles for enhancing the antifungal potential of FTN for the topical management of tinea corporis.